Quantitative dynamic 18FDG-PET and tracer kinetic analysis of soft tissue sarcomas. (August 2013) - Rusten, Espen; Rødal, Jan; Revheim, Mona E.; Skretting, Arne; Bruland, Øyvind S.; Malinen, Eirik
Abstract Purpose. To study soft tissue sarcomas using dynamic positron emission tomography (PET) with the glucose analog tracer [18F]fluoro-2-deoxy-D-glucose (18FDG), to investigate correlations between derived PET image parameters and clinical characteristics, and to discuss implications of dynamic PET acquisition (D-PET). Material and methods. D-PET images of 11 patients with soft tissue sarcomas were analyzed voxel-by-voxel using a compartment tracer kinetic model providing estimates of transfer rates between the vascular, non-metabolized, and metabolized compartments. Furthermore, standard uptake values (SUVs) in the early (2 min p.i.; SUVE) and late (45 min p.i.; SUVL) phases of the PET acquisition were obtained. The derived transfer rates K1, k2 and k3, along with the metabolic rate of 18FDG (MRFDG) and the vascular fraction νp, was fused with the computed tomography (CT) images for visual interpretation. Correlations between D-PET imaging parameters and clinical parameters, i.e. tumor size, grade and clinical status, were calculated with a significance level of 0.05. Results. The temporal uptake pattern of 18FDG in the tumor varied considerably from patient to patient. SUVE peak was higher than SUVL peak for four patients. The images of the rate constants showed a systematic pattern, often with elevated intensity in the tumors compared to surrounding tissue. Significant correlations were found between SUVE/L and some of the rate parameters. Conclusions. Dynamic 18FDG-PET may provide additional valuable information on soft tissue sarcomas not obtainable from conventional 18FDG-PET. The prognostic role of dynamic imaging should be investigated.